2004
DOI: 10.1107/s0108768104003179
|View full text |Cite
|
Sign up to set email alerts
|

Two tautomers in one crystal: 4(5)-nitro-5(4)-methoxyimidazole

Abstract: The case of prototropic annular tautomerism in an imidazole derivative has been found. The crystal structure contains a 50:50 mixture of two tautomers: 4-nitro-5-methoxyimidazole and 5-nitro-4-methoxyimidazole. The X-ray experiment actually shows the superposition of these compounds; it appears as if the structure is centrosymmetric and the N-H hydrogen atoms are disordered over two ring N atoms. Owing to the hydrogen-bond pattern, the values of their site occupation factors have to be exactly equal to 1/2. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The relatively low tautomerization barriers for polyhalogenobenzimidazoles are in a good agreement with the prototropic annular tautomerism observed in X-ray experiment as a superposition, i.e., 50:50 mixture of two tautomers 1H and 3H in the crystal structure. Such an effect is assumed as typical of centrosymmetric structures in which the N-H hydrogen atom can be disordered over two ring N atoms; 29,30 therefore it can be expected for the other halogenobenzimidazoles. The correlation between the 14 N NQR frequencies obtained in the experiment and those calculated by DFT, assuming the monomers of 1H and 3H tautomeric forms, is only fairly good (the correlation coefficients are as low as 0.897 and 0.895 and standard deviations as high as 0.554 and 0.556 MHz, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively low tautomerization barriers for polyhalogenobenzimidazoles are in a good agreement with the prototropic annular tautomerism observed in X-ray experiment as a superposition, i.e., 50:50 mixture of two tautomers 1H and 3H in the crystal structure. Such an effect is assumed as typical of centrosymmetric structures in which the N-H hydrogen atom can be disordered over two ring N atoms; 29,30 therefore it can be expected for the other halogenobenzimidazoles. The correlation between the 14 N NQR frequencies obtained in the experiment and those calculated by DFT, assuming the monomers of 1H and 3H tautomeric forms, is only fairly good (the correlation coefficients are as low as 0.897 and 0.895 and standard deviations as high as 0.554 and 0.556 MHz, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The relatively low tautomerization barriers for polyhalogenobenzimidazoles are in a good agreement with the prototropic annular tautomerism observed in X-ray experiment as a superposition, i.e., 50:50 mixture of two tautomers 1 H and 3 H in the crystal structure. Such an effect is assumed as typical of centrosymmetric structures in which the N−H hydrogen atom can be disordered over two ring N atoms; , therefore it can be expected for the other halogenobenzimidazoles.…”
Section: Resultsmentioning
confidence: 99%
“…11 Similar situations, wherein two tautomers are present in the same crystal, prevail in N-(3-hydroxysalicylidene)-4methoxyaniline, 12 3(5)-phenyl-4-bromo-5(3)-methylpyrazole 13 and 4(5)-nitro-5(4)-methoxyimidazole. 14 Form II of ranitidine hydrochloride might also exist as a mixture of eneamine and nitronic acid tautomers. 15 In this communication, we present evidence that the crystal forms of omeprazole contain different tautomeric compositions, and that the phenomenon of tautomeric polymorphism in this system also leads to further questions regarding the definition of the term polymorph itself.…”
mentioning
confidence: 99%
“…The crystal structure of histaminol was recently solved and it was shown that the compound crystallizes in the form of 5-hydroxyethylimidazole where both N(H)-atoms from the imidazole ring participate in intermolecular hydrogen bonding with the atoms from the OH group [ 39 ]. There are very few reports on co-existence of the two tautomers in the crystal structures of imidazoles [ 40 , 41 ]. To the best of our knowledge, there are no evidences for tautomerization in the solid state of 2-substituted imidazoles.…”
Section: Discussionmentioning
confidence: 99%